2007
DOI: 10.1111/j.1467-9280.2007.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Possible and Impossible Objects in Infancy

Abstract: Adults can use pictorial depth cues to infer three-dimensional structure in two-dimensional depictions of objects. The age at which infants respond to the same kinds of visual information has not been determined, and theories about the underlying developmental mechanisms remain controversial. In this study, we used a visual habituation/novelty-preference procedure to assess the ability of 4-month-old infants to discriminate between two-dimensional depictions of structurally possible and impossible objects. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…Similar findings (e.g., Caron et al, 1978;Shuwairi et al, 2007) also high light some of the behavioural changes (and the corresponding evoked poten tial changes) that allow somatosensory extemalization (Rigato et al, 2014). Rigato et al (2014) provided recent insights into how the developing nervous system establishes the external location of visual and somatosensory objects and re-maps the proximal stimulation (in receptor coordinates) into external coordinates.…”
Section: Space From Eye Movementssupporting
confidence: 53%
“…Similar findings (e.g., Caron et al, 1978;Shuwairi et al, 2007) also high light some of the behavioural changes (and the corresponding evoked poten tial changes) that allow somatosensory extemalization (Rigato et al, 2014). Rigato et al (2014) provided recent insights into how the developing nervous system establishes the external location of visual and somatosensory objects and re-maps the proximal stimulation (in receptor coordinates) into external coordinates.…”
Section: Space From Eye Movementssupporting
confidence: 53%
“…Thus, impossible objects provide unusual circumstances in which the 2-D features comprising an object are well defined whereas the overall 3-D structural interpretation of this object is incoherent. This unique object category was previously used to shed light on various domains such as long-term memory representation (e.g., Schacter, Cooper, & Delaney, 1990), development of perceptual processes in infants (e.g., Shuwairi, Albert, & Johnson, 2007), and perceptual processes that mediate the representation of 3-D information (e.g., Freud, Avidan, & Ganel, 2015). In the current study, we utilized possible and impossible objects in a multisession fMRI experimental design that allows probing the nature of the representation of objectsʼ 3-D structure in the visual cortex at the level of specific regional activity as well as at the level of distinct patterns of functional connectivity across regions.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, several studies demonstrated that the visual system of both animals (newly hatched chicks) and humans is highly susceptible to the distortions of objectsʼ 3-D structure, which underlie impossible objects (Regolin, Rugani, Stancher, & Vallortigara, 2011;Shuwairi, 2009;Shuwairi et al, 2007). This sensitivity further emphasizes the importance of 3-D interpretation for object recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies measuring looking behavior in infants younger than 5 months also suggested sensitivity to pictorial depth cues (e.g. Bhatt & Waters, 1998; Shuwairi, Albert & Johnson, 2007), while other studies could not support this finding (e.g. Tsuruhara et al 2009, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Some studies measured infants’ preferential looking and concluded that infants as young as 3-months (e.g. Bhatt & Waters, 1998) and 4-months (Shuwairi, Albert & Johnson, 2007) have sensitivity to pictorial depth cues. For example, 3-month-old infants discriminated between cubes that varied in orientation as specified by shading and line junction cues.…”
Section: Introductionmentioning
confidence: 99%